Fano effect and Andreev bound states in a hybrid superconductor-ferromagnetic nanostructure - Siqueira, E. C.; Orellana, P. A.; Cestari, R. C. [UNESP]; Figueira, M. S.; Cabrera, G. G. (Elsevier, 2015)
In this work, it is considered a hybrid nanostructure composed by a quantum dot coupled to two ferromagnetic leads and a superconductor lead. It is shown that the zero-bias transmittance for the co-tunneling between the ferromagnetic leads presents Fano anti-resonances due to the destructive interference between the two spin channels mixing by the relative orientation of the magnetizations in the leads. When the superconductor is coupled to the system, electron-hole correlations between different spin states lead to a resonance in the place of the dip appearing in the transmittance. Such an effect is accompanied by two Fano anti-resonances explained by a leakage of conduction channels from the co-tunneling to the Andreev transport. In the non-equilibrium regime, correlations within the quantum dot introduce a dependence of the resonance condition on the finite bias applied to the ferromagnetic leads. However, it is still possible to observe signatures of the same interference effect in the electrical current.